2010
DOI: 10.1016/j.biombioe.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels and their by-products: Global economic and environmental implications

Abstract: The biofuel industry has been rapidly growing around the world in recent years. Several papers have used general equilibrium models and addressed the economy-wide and environmental consequences of producing biofuels at a large scale. They mainly argue that since biofuels are mostly produced from agricultural sources, their effects are largely felt in agricultural markets with major land use and environmental consequences. In this paper, we argue that virtually all of these studies have overstated the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(118 citation statements)
references
References 6 publications
3
109
0
6
Order By: Relevance
“…The empirical analysis of Serra et al suggests that in periods of high corn prices, the price of corn becomes the dominant factor in price determination. This complements the results of references [5] and [6], both of whom suggest that when the price of ethanol does not fully adjust to the rise in the price of corn, the corn biorefineries may suffer losses when corn prices are high. Similar techniques were used by Zhang et al, who investigated the volatility of the wholesale prices of corn, ethanol, soybeans, gasoline, and oil in the United States between March 1989 and December 2007 [7].…”
Section: Literature Reviewsupporting
confidence: 83%
“…The empirical analysis of Serra et al suggests that in periods of high corn prices, the price of corn becomes the dominant factor in price determination. This complements the results of references [5] and [6], both of whom suggest that when the price of ethanol does not fully adjust to the rise in the price of corn, the corn biorefineries may suffer losses when corn prices are high. Similar techniques were used by Zhang et al, who investigated the volatility of the wholesale prices of corn, ethanol, soybeans, gasoline, and oil in the United States between March 1989 and December 2007 [7].…”
Section: Literature Reviewsupporting
confidence: 83%
“…A similar situation arises with biodiesel production from oilseeds. Taheripour et al (2008) show that ignoring the by-products of biofuels leads researchers to significantly overstate the impact of mandates. They incorporate DDGS and vegetable oil cake (soybean meal in the US and rapeseed cake in EU) and introduce substitution between biofuel by-products and other animal feed in livestock production.…”
Section: Methodsmentioning
confidence: 99%
“…The early papers published in this area suggested that the USA corn ethanol program could cause major land use implications [4][5][6]. However, the more recent studies find that the early estimates have overstated the land use implications of this program [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This global CGE model, developed at the Center for Global Trade Analyses, has played a leading role in estimating biofuel induced land use changes. Several studies have used this model to evaluate iLUC emissions due to biofuels [7,[10][11][12]17,18]. This model uses two different land transformation elasticities to govern the supply of land in each region.…”
Section: Introductionmentioning
confidence: 99%